An orthogonal seryl-tRNA synthetase/tRNA pair for noncanonical amino acid mutagenesis in Escherichia coli. Issue 20 (15th October 2020) - Zambaldo, Claudio; Koh, Minseob; Nasertorabi, Fariborz; Han, Gye Won; Chatterjee, Abhishek; Stevens, Raymond C.; Schultz, Peter G.
Graphical abstract: Abstract: We report the development of the orthogonal amber-suppressor pair Archaeoglobus fulgidus seryl-tRNA (Af-tRNA Ser )/ Methanosarcina mazei seryl-tRNA synthetase (MmSerRS) in Escherichia coli . Furthermore, the crystal structure of MmSerRS was solved at 1.45 Å resolution, which should enable structure-guided engineering of its active site to genetically encode small, polar noncanonical amino acids (ncAAs).